Correction: Trehalose-cored amphiphiles for membrane protein stabilization: importance of the detergent micelle size in GPCR stability - Das,M; Du,Y; Mortensen,JS; Ramos,M; Ghani,L; Lee,HJ; Bae,HE; Byrne,B; Guan,L; Loland,CJ; Kobilka,BK; Seok,Chae P (Organic and Biomolecular Chemistry, 2019)
Correction for ‘Trehalose-cored amphiphiles for membrane protein stabilization: importance of the detergent micelle size in GPCR stability’ by Manabendra Das et al., Org. Biomol. Chem., 2019, 17, 3249–3257.